2018
DOI: 10.1002/chem.201803940
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Atypical Fluorine–Hydrogen Bonds and Their Effects on Nucleoside Conformations

Abstract: The ability of fluorine to serve as a hydrogen-bond acceptor has been debated for many years. Short fluorine-hydrogen contacts are thought to play a key role in stabilizing some complex supramolecular systems. To directly probe the existence of fluorine-hydrogen bonds, we have performed NMR spectroscopy and computational modeling on a series of C2'-fluorinated nucleosides. Specifically, quantum mechanics/molecular mechanics (QM/MM) analysis and [ F, H] HMBC NMR experiments provided direct evidence for a C-H⋅⋅⋅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…However, the role of the geminal fluorines in the CF 2 H moiety as HB acceptors received no attention in the literature, when describing this group as a bioisostere of OH and SH. Although scientists have debated for decades regarding the existence of HB interactions of the type C–F ... H–X, i.e., when fluorine acts as an HB acceptor, an increasing number of studies in recent years, indeed, show that such interactions do exist, mainly, intramolecularly, or in cases in which the fluorine atom is located in close proximity to an HB donor, such as in ligand–receptor interactions . Therefore, this type of HB interactions, which is much higher in the OH group (versus SH and CF 2 H), via the oxygen lone pair electrons, should be taken into account when dealing with the CF 2 H as a bioisostere of OH or SH.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the role of the geminal fluorines in the CF 2 H moiety as HB acceptors received no attention in the literature, when describing this group as a bioisostere of OH and SH. Although scientists have debated for decades regarding the existence of HB interactions of the type C–F ... H–X, i.e., when fluorine acts as an HB acceptor, an increasing number of studies in recent years, indeed, show that such interactions do exist, mainly, intramolecularly, or in cases in which the fluorine atom is located in close proximity to an HB donor, such as in ligand–receptor interactions . Therefore, this type of HB interactions, which is much higher in the OH group (versus SH and CF 2 H), via the oxygen lone pair electrons, should be taken into account when dealing with the CF 2 H as a bioisostere of OH or SH.…”
Section: Results and Discussionmentioning
confidence: 99%
“…H-bonds play a pivotal role in many biological systems and are deeply involved in the activity of numerous drugs and biologically active compounds. At the interface between H-bonding and the fluorine effects, one can find two important topics: (1) the intrinsic ability of fluorine functions to act as H-bond donors (e.g., CF 2 H group) ,, or acceptors (via the lone pair electrons of fluorine known as very weak acceptors; such interactions exist, mainly, in cases in which the fluorine atom is located in close proximity to a HB donor) and (2) the influence of fluorine functions on the hydrogen bonding capacity of other functional groups (FGs). For instance, the influence of one or more fluorine atoms on the H-bond acidity (p K AHY ) of hydroxyl groups in various conformationally flexible or rigid substrates was thoroughly investigated by Linclau and Graton and co-workers, who showed that this property can be tuned, up or down, depending on molecular structural motifs such as an intramolecular H-bond (IMHB) and conformational preference or rigidity (Figure A). , However, the effect of fluorine atom(s) on the H-bond basicity (p K HB ) of the adjacent functional groups, i.e., at the α position, has not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal was kept at 150 K during data collection. The structure was solved with the ShelXT structure solution program using intrinsic phasing and refined with the XL refinement package using least squares minimization . Structural assignments of nucleosides were obtained from gCOSY, gHSQC, and gHMBC NMR experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Due to this limitation, we adopted two approaches to increase the thermal stability of ONA/RNA duplexes: (i) introduction of additional functional groups in the oxepane ring to steer the sugar conformation that may favor binding to RNA (e.g., OxT 1 ; Scheme ) and (ii) moving the location of phosphodiester backbone closer to the nucleobase to better mimic the native DNA or RNA backbone, e.g., 4′-7′ and 3′-7′ linked ONAs (OxT 2 and OxT 3 ; Scheme ). The choice of the nucleosides, alone or inside a duplex, is guided by classical molecular dynamics (MD) simulations and quantum mechanical calculations as reported recently by our groups. , Herein, we present the stereoselective functionalization of the unsaturated oxepine nucleosides, their elaboration into phosphoramidite derivatives by careful selection of orthogonal protecting groups, and microwave-assisted phosphitylation of their sterically hindered hydroxyl groups. We also describe the incorporation of oxepane nucleoside units into DNA and RNA strands via solid-phase synthesis and the impact of these modifications on the structure and thermal stability of dsRNA, dsDNA, and RNA–DNA hybrid duplexes.…”
Section: Introductionmentioning
confidence: 99%